2020
DOI: 10.2478/raon-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on cancer diagnosis and management in Slovenia – preliminary results

Abstract: BackgroundThe COVID-19 pandemic has disrupted the provision and use of healthcare services throughout the world. In Slovenia, an epidemic was officially declared between mid-March and mid-May 2020. Although all non-essential health care services were put on hold by government decree, oncological services were listed as an exception. Nevertheless, as cancer control depends also on other health services and additionally major changes in people’s behaviour likely occurred, we aimed to analyse whether cancer diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
88
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(110 citation statements)
references
References 15 publications
12
88
0
4
Order By: Relevance
“…For example, previous research has indicated that the rate of stroke [ 11 ], acute heart failure [ 12 ], and pulmonary embolism diagnoses [ 13 ] has fallen during the COVID-19 pandemic, which may be explained by a decrease in the proportion of symptomatic patients seeking medical care. Several studies have also shown that the incidence of cancer has decreased during lockdown in a number of countries [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Some cancer diagnoses might have been more affected by the COVID-19 than other cancer diagnoses, and cancers detected in the context of screening programs might have been particularly impacted.…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous research has indicated that the rate of stroke [ 11 ], acute heart failure [ 12 ], and pulmonary embolism diagnoses [ 13 ] has fallen during the COVID-19 pandemic, which may be explained by a decrease in the proportion of symptomatic patients seeking medical care. Several studies have also shown that the incidence of cancer has decreased during lockdown in a number of countries [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Some cancer diagnoses might have been more affected by the COVID-19 than other cancer diagnoses, and cancers detected in the context of screening programs might have been particularly impacted.…”
Section: Introductionmentioning
confidence: 99%
“…Fear and anxiety associated with COVID-19 caused the patients to delay their treatment by disrupting adherence to therapy [ 22 ]. In addition, delaying diagnostic tests was another issue during pandemic leading to the presentation of cancer patients at advanced stage [ 20 , 21 ]. Guven et al evaluated the effect of COVID-19 on admissions of cancer patients and determined that there was a significant decrease in the number of newly diagnosed cancer cases when compared with the previous year [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…De Vincentiis et al reported that the average number of newly diagnosed cancer patients in the 2018–2019 period decreased by approximately 39% during the 2020 pandemic period [ 21 ]. Similarly, another study conducted in Slovenia showed that diagnostic-screening tests and newly diagnosed cancer patients decreased in the COVID-19 pandemic [ 20 ]. In all four experienced centers included in this study, the number of newly diagnosed patients during the pandemic process decreased significantly compared with the previous year as of in our study, in correlation to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged clinical trial closure does not appear to be warranted. Third, early detection of cancer is crucial for secondary cancer prevention [ [72] , [73] , [74] ]. Screening for high-risk populations must be firmly implemented in accordance with the guidelines.…”
Section: Adjustments Of Cancer Treatment Paradigm In the Covid-19 Eramentioning
confidence: 99%